The Effect of Digital Literacy-Based Learning on Student Motivation and Socialization Ability - Sri Wahyuni; Yesi Novitasari; Suharni Suharni; Reswita Reswita (Consilium : Berkala Kajian Konseling dan Ilmu Keagamaan, 2022)
Online learning programs require students to use digital literacy. The question is how does digital literacy affect student learning motivation, then does it also affect students' ability to socialize. The purpose of the study was to describe the level of digital literacy, learning motivation and social skills of FKIP students at Lancang Kuning University. The research methodology used is descriptive analysis with hypothesis testing using regression. The number of samples is 99 students who are drawn by total sampling from all respondents. The results showed that 1) the digital literacy level of students was at a moderate level. 2) low student learning motivation. 3) students' social skills are low. 4) there is a positive influence between digital literacy on the learning motivation of FKIP students. 5) there is a positive influence between digital literacy on the social skills of FKIP students at Lancang Kuning University. The implications of this research are as material for consideration for counselors in providing services to students who have an impact on digital literacy on learning motivation and social skills.